Bibliotecas, leituras e leitores : um estudo no contexto da UFMT - Freitas, Carlos Henrique Tavares de (2012)
The Technologies of the Information and Communication are important elements for the access to the information, the production of new knowledge and the scientific development, being present also in the context of the higher education and in the environment of the academical libraries, as much as resources of computerize of the technical services and of the administration of these Units, as in the development of products and services based on digital contents of information. Thereby, this study has for objective to investigate the readers' characteristics and of the reading types developed at the Central Library of the Mato Grosso Federal University, considering that, nowadays, the reading resources and traditional research divide space with new products and services, influenced by the Technologies of the Information and Communication. Accordingly it involves an exploratory research based in a qualitative approach, tends as instruments of collection of data, the observation, the questionnaire, the structured interview and the participant observation. The field research was divided in two main stages, the first main was the elaboration of a socioeconomic and cultural profile, and the second stage was the accomplishment of interviews and observations of the processes of navigation of the users/readers of the library. In the first stage, among other aspects, we observed that the readers of the Central Library correspond to a diversified and dynamic public, composed, in its majority for students of degree courses that they are registered in the Pergamum System. Most of the users/readers uses the library frequently, being also verified a significant amount of visitors that use the environment study for contests and similar. The academic research corresponds to the largest reason of use of the library and, and the products and services, it was observed that the books, the local consultation, the service of circulation of bibliographical materials and the use of the atmosphere for study are the resources more used by the readers, having a low index of use of the Technologies of the Information and Communication in the environment of the library, like of the computerized services. The second phase of the investigation understood three moments: approach of the subjects (when it happened the scheduling of the interviews and observations), structured interview and participant observation. The interviews involved questions about the readers' characteristics, their relationships with the technologies, with the cyberspace, products and services of the Central Library. The participant observation explored the solution of three navigation problems proposed to those researched: the accomplishment of a generic research, the accomplishment of an academic research and the exploration of the on-line services of the Central Library (researches in the electronic catalog, reservations, renewals etc.). It was concluded that all of the users researched in this stage of the study presented characteristics of immersive readers, but some readers also stand out like a meditative readers, and these profiles are influenced by the atmosphere, situation and research objectives, as them culture. Besides, on the hand, the fact of they be immersive readers it doesn't mean that they prefer just use the cyberspace, to the detriment of the books and too much materials printed papers, this same prerogative doesn't also mean that these readers know, they dominate and they use the electronic services of the Central Library of UFMT thoroughly.